Respuesta :
Answer:
Solve by mathematical induction.
Step-by-step explanation:
Let [tex]a_1,a_2, \ldots, a_k[/tex] be integers with [tex]GCD(a_1,a_2, \ldots ,a_k) = 1[/tex].
We need to prove that
[tex]a_1u_1 + a_2u_2 + \ldots + a_ku_k = 1[/tex]
has a solution in integers [tex]u_1,u_2, \ldots, u_k \in \mathbb{Z}.[/tex]
To do so, we will use mathematical induction.
The base case
Consider the case for [tex]n=2[/tex]. Then,
[tex]GCD(a_1,a_2) = 1[/tex]
and we need to prove that
[tex]a_1u_1 + a_2u_2 = 1[/tex].
Since the largest positive integer dividing [tex]a_1[/tex] and [tex]a_2[/tex] is 1, by the Euclidean algorithm, we have
[tex]\left( \exist u_1, u_2 \in \mathbb{Z}\right) a_1u_1 + a_2u_2 = 1[/tex]
Therefore, the statement is true for [tex]n=2[/tex].
The induction step
This step proves that if the property holds for one natural number [tex]n[/tex], then it holds for the next natural number [tex]n+1[/tex]. Combined wit the base case, it will establish the property for [tex]\forall n \in \mathbb{N}.[/tex]
Now, suppose that the statement is true for [tex]n=k[/tex].
This means that
[tex]GCD(a_1, a_2, \ldots, a_k) = 1 \implies \left( \exists u_1, u_2, \ldots u_k \in \mathbb{Z}\right) a_1u_1 + a_2u_2 +\ldots+ a_ku_k = 1[/tex]
Let's check if the statement holds true for the next natural number, that is [tex]n= k+1[/tex].
[tex]GCD(a_1, a_2, \ldots, a_{k+1}) = 1 \implies GCD(a_1, a_2, \ldots, a_k) = 1 \: \wedge \: GCD(a_k, a_{k+1}) = 1[/tex]
By the Euclidean algorithm, we have
[tex]GCD(a_1, a_2, \ldots, a_{k}) = 1 \implies \left(\exists u_1,u_2, \ldots, u_k \in \mathbb{Z}\right)a_1u_1 + a_2u_2 + \ldots + a_ku_k = 1[/tex]
and
[tex]GCD(a_k, a_{k+1}) = 1 \implies \left(\exists u_1,u_2, \in \mathbb{Z}\right)a_ku_k + a_{k+1}u_{k+1} = 1[/tex]
Now, multiply the obtained equations.
[tex](a_1u_1 + a_2u_2 + \ldots + a_ku_k)(a_ku_k + a_{k+1}u_{k+1}) = 1 \cdot 1[/tex]
Removing parenthesis gives
[tex]a_1u_1 \cdot a_ku_k + a_2u_2\cdot a_ku_k + \ldots + a_ku_k \cdot a_ku_k +\\a_1u_1 \cdot a_{k+1}u_{k+1} + a_2u_2\cdot a_{k+1}u_{k+1} + \ldots + a_ku_k \cdot a_{k+1}u_{k+1} =1[/tex]
Now, collect up the terms by [tex]a_1, a_2, \ldots, a_{k+1}[/tex].
[tex]a_1\underbrace{(u_1 a_ku_k +u_1 \cdot a_{k+1}u_{k+1})}_{\in \mathbb{Z}}+ a_2\underbrace{(u_2 a_ku_k+ u_2 a_{k+1}u_{k+1} )}_{\in \mathbb{Z}} + \ldots + a_{k+1}\underbrace{(a_ku_k u_{k+1})}_{\in \mathbb{Z}} \\ =1[/tex]
Now, denote
[tex]u'_1 =u_1 a_ku_k +u_1 \cdot a_{k+1}u_{k+1},u'_2=u_2 a_ku_k+ u_2 a_{k+1}u_{k+1}, \ldots, u'_{k+1} =a_ku_ku_{k+1}[/tex]
Therefore,
[tex]\left(\exists u'_1,u'_2, \ldots, u'_{k+1} \in \mathbb{Z}\right)a_1u'_1 + a_2u'_2 + \ldots + a_{k+1}u'_{k+1} = 1[/tex]
Hence, the equation
[tex]a_1u_1 + a_2u_2 + \ldots + a_ku_k = 1[/tex]
has a solution in integers [tex]u_1,u_2, \ldots, u_k \in \mathbb{Z}.[/tex]